POST THYROIDECTOMY HYPOCALCEMIA DOES ARTERIAL LIGATION PLAY A SIGNIFICANT ROLE? Post Thyroidectomy Hypocalcemia - Khan, Jahangir Sarwar; Bhopal, Faisal G.; Hassan, Hamid; Iqbal, Mohammad (Pakistan Armed Forces Medical Journal, 2008)
Objective: The aim of this study was to determine if bilateral inferior thyroid artery (ITA) ligation is a causal factor for the occurrence of postoperative hypocalcaemia after subtotal thyroidectomy. Study design: Quasi experimental trial. Place and duration of study: One year study from Jan 2005 to Dec 2005 conducted at surgical department of Rawalpindi General Hospital (UNIT–I). Patients and Methods: One hundred patients were included in the study who underwent subtotal thyroidectomy with and without truncal ligation of inferior thyroid artery and were prospectively analyzed comparing postoperative and late serum calcium levels. Result: A significant incidence of postoperative hypocalcaemia occurred: more in Group A (48%) as compared to Group B (22%). This difference was statistically significant shown by the P value < 0.5 on the 1st postoperative day in patients with ligation of inferior thyroid artery. Conclusion: The ligation of the ITA tends to produce hypocalcaemia in patients undergoing subtotal Thyroidectomy.